Investigating Outcomes of Adolescents and Young Adults (10–24 Years of Age) Lost to Follow-up from Tuberculosis Treatment in Gaborone, Botswana. Issue 10 (October 2019) - Enane, Leslie A.; Lowenthal, Elizabeth D.; Arscott-Mills, Tonya; Eby, Jessica; Caiphus, Cynthia; Kgwaadira, Botshelo; Coffin, Susan E.; Steenhoff, Andrew P.
Abstract : This retrospective study investigated outcomes among lost to follow-up (LTFU) adolescents and young adults (AYAs: 10–24 years of age) with tuberculosis (TB) registered from 2008 to 2014 in Gaborone, using surveillance data. Of 68 LTFU AYAs, 16 repeated treatment; 8 completed and 6 were again LTFU. Of 4 confirmed deaths, 3 had TB/HIV coinfection. Approaches to improve AYA retention in TB care are needed.